Analisis Manajemen Pajak Pada Industri Penyedia Jasa Telekomunikasi - Iim Ibrahim Nur (Ultima Management : Jurnal Ilmu Manajemen, 2010)
Tax Management must be done throughout the company’s activities. In principle, tax management can be done via good tax compliance and minimizing tax burden. The latter can be achieved by transforming non-deductible expenses into deductible expenses. For example, PT Nyambung Teruuusss Tbk. (PT. NT) must change income Tax Art. 21 paid by the company into tax allowance with gross-up method, pooling company's cars at the office instead of letting these cars brought home by the employees, outbound training for employees instead of family gathering, and other methods including converting fringe benefits into allowance. Another method to minimize tax burden is to change depreciation methods into double-declining method instead of straight-line method. With nondeductible transformation method have saved PT NT Rp 5.26 billion of corporate income tax, while depreciation methods transformation is predicted to save the company Rp 735.66 billion for an eightyear period